Infectious and Non-Infectious Diseases in Manatees in Brazil - Attademo, Fernanda Loffler Niemeyer; Oliveira, Radan Elvis Matias de; de Sousa, Gláucia Pereira; Luna, Fábia Oliveira (Acta Scientiae Veterinariae, 2020)
Background: Antillean manatee (Trichechus manatus) and Amazonian manatee (Trichechus inunguis) are the two species of manatees that occur in Brazil, and both are endangered. Studies on manatee disease in Brazil were previously based mainly on Florida manatees. In recent years, these studies have increased in Brazil. Thus, the objective was to carry out a survey of the publications of infectious and non-infectious diseases in the two species of manatees that occur in the country, to assist in the identification of threats to the species and in the health assessment of manatees in the country. Review: Regarding infectious and contagious diseases, parasites have affected both species of manatees in Brazil, such as Pulmonicola cochleotrema in wild T. manatus, Toxoplasma gondii in both species, and Cryptosporidium spp. also in both species, this being an important agent of zoonotic character. Giardia sp., another zoonotic parasite, has also been reported in both species of manatees in Brazil. Mycotic lesions caused by B. hawaiiensis have been described in calves of T. manatus in captivity. Meanwhile, Candida sp., Trichosporon sp., Rhodotorula sp., and Cryptococcus sp. have been identified in T. inunguis. Studies on viruses in manatees are still not widespread compared to other species; however, it has been verified that rotavirus is present in T. manatus in captivity. In studies carried out to identify bacteria in T. manatus, the following bacteria were isolated: Arizona sp., Bacillus sp., Corynebacterium equi, Corynebacterium pseudodiphteriticum, Corinebacterium sp., Edwasiella tarda, Enterobacter aerogenes, Enterobacter agglomerans, Enterobacter sakasakii, Escherichia coli, Leptospira spp., Proteus sp., Proteus vulgaris, Providencia rettgeri, Pseudomonas aeruginosa, Salmonella spp., Serratia marcescens, Staphylococcus sp., Staphylococcus aureus, Staphylococcus coagulase-negativa, Stenotrophomonas maltophilia, Streptococcus sp., and Streptococcus viridans. Regarding noninfectious diseases, food-related diseases stand out, where gastrointestinal complications in manatees and obesity in animals in captivity are among the highest occurrences. Intestinal tympanism was reported in a T. inunguis calf, causing death of the animal. Pollution and contamination have also been a concern for the health of these animals. In studies carried out with T. manatus in Paraíba state, accumulation of heavy metals in the animals was verified, possibly originating from sugarcane farms in the region. The ingestion of garbage has also been one of the greatest threats to the health of manatees, where it was registered as a possible cause of death of T. inunguis in Amazonas state. Regarding congenital diseases, although rare in manatees, two calves of T. manatus in Ceará state have been described as having congenital malformations in the heart and brain, without a well-defined etiology. Trauma has been affecting both species; in Brazil, 17.3% of manatees reintroduced by 2018 showed evidence of collisions with vessels. Hunting for T. inunguis still occurs frequently, which has been greatly reduced for T. manatus. Conclusion: Pathogens and other factors that affect manatees have a potential impact on both species. Some of the identified agents have a zoonotic potential and, therefore, are also public health issues. This survey demonstrates that the need for incentives for studies on health assessment and pathogens in these species, both in the wild and in captivity, should be encouraged.